2010
DOI: 10.1097/ccm.0b013e3181d4502e
|View full text |Cite
|
Sign up to set email alerts
|

Infectious risk associated with arterial catheters compared with central venous catheters*

Abstract: After participating in this activity, the participant should be better able to:1. Illustrate factors associated with arterial catheter-related colonization.2. Explain risk factors associated with central venous catheter-associated colonization.3. Use this information in a clinical setting.Unless otherwise noted below, each faculty or staff's spouse/life partner (if any) has nothing to disclose.Dr. Timsit has disclosed that he received grants/research fees from Jousea-Cilog, Pfizer, and MSD; was a consultant/ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
2
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 28 publications
1
73
2
10
Order By: Relevance
“…We found a higher incidence of colonization than for non-RRT catheters [e.g., 11.1 per 1000 catheter-days were reported in Lucet et al (15)], but paradoxically the incidence of clinically important catheter-related bloodstream infection was proportionally low. Using the equation derived from 29 papers of non-RRT catheters (16): BSI ϭ 0.73 ϩ 0.17 CTC (where BSI denotes bloodstream infection and CTC denotes colonization incidences), we would have expected 7.3 catheter-related bloodstream infection per 1000 catheter-days, which lies outside our 95% CI.…”
Section: Discussionmentioning
confidence: 71%
“…We found a higher incidence of colonization than for non-RRT catheters [e.g., 11.1 per 1000 catheter-days were reported in Lucet et al (15)], but paradoxically the incidence of clinically important catheter-related bloodstream infection was proportionally low. Using the equation derived from 29 papers of non-RRT catheters (16): BSI ϭ 0.73 ϩ 0.17 CTC (where BSI denotes bloodstream infection and CTC denotes colonization incidences), we would have expected 7.3 catheter-related bloodstream infection per 1000 catheter-days, which lies outside our 95% CI.…”
Section: Discussionmentioning
confidence: 71%
“…However, in a prospective study 25 of 212 intensive care unit patients with placement of both arterial and central venous catheters, the cumulative incidence of catheter-related BSI for arterial catheters was 7.7%, comparable to an incidence of 9.4% for central venous catheters (P=.45). Several studies [9][10][11] confirmed that risk for infection associated with arterial catheters was similar to the risk associated with central venous catheters. Thus, prevention of catheter-related BSI has become an important issue in medical practice.…”
Section: Discussionmentioning
confidence: 67%
“…Catheter-related bloodstream infections (BSIs) are a common and serious complication of intravascular catheters and are associated with increased morbidity, mortality, length of hospital stay, and medical costs. [1][2][3][4][5] Although previous studies [6][7][8] indicated a low risk for infections associated with use of arterial catheters, recent studies [9][10][11] showed that the risk for arterial catheter-related infection was high, comparable to the risk associated with short-term use of central venous catheters. Compared with adult patients, children are more susceptible to nosocomial infection, and catheter-related BSI is considered the most common nosocomial infection in pediatric intensive care units (PICUs).…”
mentioning
confidence: 88%
“…Major complications occur in < 1% of cases, therefore arterial lines are deemed to be a safe procedure [4]. However, there are many cases reported of accidental injection into arterial lines with significant complications, with patients developing necrosis and requiring debridement of ischaemic areas [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Blood spillage, exsanguination and bacterial contamination are other potential complications when using the standard three-way tap [3]. It is not commonly appreciated that arterial cannulae are prone to colonisation and infection at a similar rate to central venous catheters [4]. No real solutions have been proposed to these problems.…”
Section: Introductionmentioning
confidence: 99%